Analysis of Public Perception Regarding Public Service Information in Helvetia Village - Risda Mega Riana Br Sembiring; Miftha Rizkina; Ayu Kurnia Sari (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to analyze public perception regarding the effectiveness of public service information delivery in Helvetia Village through a hybrid information system (announcement boards and WhatsApp) based on the Good Governance framework (Transparency and Accountability). The method used is descriptive qualitative with triangulation data collection techniques including in-depth interviews, observation, and documentation. The results indicate that public perception of the information delivery system tends to be poor, triggering the "back-and-forth" (bolak-balik) phenomenon among residents. This failure is caused by two structural factors: transparency failure because the system does not provide specific-situational information content, and an accountability crisis due to the inconsistency of officials in fulfilling post-service follow-up promises. The value of this research lies in identifying that service effectiveness depends not only on media availability but on the quality of substantive content and the certainty of service process accountability. This study contributes to village-level officials in designing more responsive public communication strategies.